Dopaminergic neuronal death in the substantia nigra associates with change in serum levels of TNF-α and IL-1β; evidence from early experimental model of Parkinson's disease. (3rd June 2022) - Piri, Hossein; Sharifi, Sahar; Nigjeh, Sepideh; Haghdoost-Yazdi, Hashem
ABSTRACT: Purpose: Studies have shown that inflammation plays a key role in etiology of Parkinson's disease (PD). However, human studies which have evaluated association between PD and serum levels of tumor necrosis factor-alpha (TNF-α) and interleukin-1 beta (IL-1β) have reported conflicting results. In this study, serum and striatum levels of these cytokines were evaluated in 6-hydroxydopamine (6-OHDA) animal model of PD. Method: The neurotoxin of 6-OHDA was injected into medial forebrain bundle of right hemisphere and behavioral tests were carried out to eight weeks thereafter to evaluate severity of PD and its progress. Blood was collected before the toxin and in second and eight weeks after that. Survival of dopaminergic (DAergic) neurons in substantia nigra was assessed by immunohistochemistry. TNF-α and IL-1β levels were determined using ELISA kits. Result: Severity of behavioral symptoms was gradually increased in 6-OHDA-treated rats. They showed a decrease in serum TNF-α level in the eight week and increase in IL-1β both in the second and eight weeks. They were divided into two subgroups, symptomatic and asymptomatic with severe and moderate degrees in DAergic neuronal death. Significant decrease in serum TNF-α was only observed in the symptomatic subgroup but IL-1β increased in both subgroups. Also, striatal levels of both cytokines were higher in the lesioned hemisphere. Conclusion: Increase in serum IL-1β level can reflect moderate degree of lesion in substantia nigra and thereby is used for prognosis of PD before its clinical symptoms are appeared. On the other hand, an increase in serum TNF-α is appeared in advanced stage of PD.